Implementasi Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Terkait Ketidaksesuaian Jam Kerja Pegawai - Asyifa Permata Dewi; Ariqah Nur Faizah; Dita Rahmaditiani J; Salwa Khoirunnisa; Sri Nadya Nurviani; Izzatusholekha (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the extent to which the implementation of law number 13 of 2003 concerning employment is related to the discrepancy in employee working hours at pt. Aice and pt. Adi putra denpasar and also to find out whether in practice there are any obstacles in the application of law number 13 of 2003 concerning manpower related to the mismatch of employee working hours. This study used the literature study research method, the data generated by collecting references from sources, books, and journals related to the topics raised in this study. The results of this study indicate that the two companies are proven to still violate regulations, especially in the discrepancy in working hours of employees. In the future, it is hoped that all companies will be able to fulfill their obligations in fulfilling the rights of employees so that employees can feel comfortable and be appreciated.